2023
DOI: 10.1158/1538-7445.am2023-2850
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2850: NX-5948 promotes selective, sub-nanomolar degradation of inhibitor-resistant BTK mutants

Abstract: Small molecule kinase inhibitors have revolutionized the treatment of hematological malignancies by suppressing signaling pathways essential for tumor cell survival. Bruton’s Tyrosine Kinase (BTK) inhibitors are widely used in the clinic for treatment of patients with B cell malignancies. Acquired resistance mutations, however, can reduce or eliminate their efficacy and represent a growing challenge. Mutations at C481 dramatically reduce the binding of covalent BTK inhibitors, whereas other clinically-observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…48 In these cases, small molecule-induced protein degradation may allow for continued targeting of BTK. 49 The novel agent NX-5948 is a chimeric targeting molecule that contains a BTK hook linked to a cereblon harness and allows for ubiquitylation and proteasomal degradation of BTK. 50 Preclinical studies have shown successful degradation of BTK, even in models with BTK C481S mutations.…”
Section: Btk Degradersmentioning
confidence: 99%
“…48 In these cases, small molecule-induced protein degradation may allow for continued targeting of BTK. 49 The novel agent NX-5948 is a chimeric targeting molecule that contains a BTK hook linked to a cereblon harness and allows for ubiquitylation and proteasomal degradation of BTK. 50 Preclinical studies have shown successful degradation of BTK, even in models with BTK C481S mutations.…”
Section: Btk Degradersmentioning
confidence: 99%
“…82 Both PROTACs were efficient in C481S mutated cells, NX-5948 was proven to induce also degradation of other forms of mutated BTK (T474I, V416L and L528W). 83,84 Expectedly, NX-2127 degraded BTK also in patients who have acquired BTK resistance mutations as a result of prior BTK inhibitor therapies. 35…”
Section: Protacsmentioning
confidence: 99%
“…Moreover, NX‐2127 possesses dual degradation mechanism, and besides BTK can target other clinically validated proteins: transcription factors Aiolos (IKZF3) and Ikaros (IKZF1) regulating T‐cells function 82 . Both PROTACs were efficient in C481S mutated cells, NX‐5948 was proven to induce also degradation of other forms of mutated BTK (T474I, V416L and L528W) 83,84 . Expectedly, NX‐2127 degraded BTK also in patients who have acquired BTK resistance mutations as a result of prior BTK inhibitor therapies 35…”
Section: Protacsmentioning
confidence: 99%